PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN PRODUK INDIHOME DI KOTA SURABAYA - Benge, Wilhemus Dionysius Mario Randy; Nugroho, Rusdi Hidayat (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Entering the era of the industrial revolution 4.0, human life will never be separated from the existence of technology. Currently the internet network has become a primary need for humans. This indirectly opens up business opportunities for internet network provider companies, especially in Indonesia. Indihome as one of these companies, is required to provide and maintain their best service quality so that they can provide a positive brand image to the public. This will ultimately foster customer loyalty which will help Indihome in an effort to maintain their market share. This study aims to examine whether service quality and brand image have a simultaneous and partial influence on Indihome customer loyalty in the city of Surabaya. The number of samples used were 120 respondents who were determined using the Accidental Sampling method. The data analysis technique used multiple linear regression analysis. The results of the analysis show that service quality and brand image simultaneously and partially have a positive effect on customer loyalty